Differences in predictive and prospective control strategies by batting skill level during an interception task - Sun, Yu; Jang, Dukchan (Frontiers in Psychology, 2025)
IntroductionSuccessful interception of fast-moving objects requires both predictive control and online processing of visuomotor information. However, it remains unclear how expertise influences the use of late trajectory information when access to the final portion of the trajectory is restricted. This study investigated skill-level differences in visuomotor coordination under conditions limiting access to the latter portions of a moving stimulus trajectory.MethodsTwenty participants (10 novices, 10 experts) performed a touchscreen-based interception task involving varying stimulus velocities (0.5, 0.67, and 1.0 m/s) and visibility conditions (stimulus-unhidden vs. stimulus-hidden). Participants tracked a horizontally moving target and attempted to intercept it at a designated target area using a stylus. Eye and hand movement data were recorded to assess gaze behavior, motor accuracy, and eye-hand coordination.ResultsExperts exhibited significantly shorter saccadic latencies, longer gaze durations, and lower gaze error compared to novices. They also demonstrated greater hand accuracy and faster response times, with smaller timing and radial errors. Moreover, eye-hand coupling was more efficient in experts, with shorter temporal coupling and tighter spatial coordination—particularly under stimulus-hidden conditions.ConclusionsThese findings suggest that expertise enhances the integration of perceptual and motor processes, supporting more precise and timely responses. Experts also processed limited visual information more effectively and made better use of online feedback, demonstrating that skilled perception-action coupling relies on flexible integration of predictive planning and online feedback.